Strategi Pemanfaatan E-Commerce untuk Meningkatkan Daya Saing Ekspor UMKM Craft di Indonesia - Aji Prasojo; Yogi Dwi Lestari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to explore the strategic role of e-commerce in increasing the export of handicraft products by Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, with a case study on CV. Palm Craft in Kediri. In the context of globalization and digitalization, e-commerce is an important means for MSMEs to reach the international market, especially in the midst of the challenges of the COVID-19 pandemic that limit conventional export activities. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The main focus of this study is how CV. Palem Craft utilizes various digital platforms such as social media (Instagram, Facebook), marketplaces (Tokopedia, Shopee), and global platforms (Amazon, Etsy) to expand market access, build product branding, and increase the selling value of local handicrafts. The results of the study show that the strategic use of e-commerce has helped companies overcome export barriers such as limited distribution networks, logistics constraints, and lack of international promotion. In addition, e-commerce also allows CVs. Palem Craft to build direct relationships with global consumers, get faster feedback, and make product adjustments according to market needs. This research also identifies supporting factors such as digital literacy, product quality, and production capacity as crucial aspects in the success of e-commerce strategies. The implications of this study provide relevant insights for other MSMEs that want to develop exports through the use of digital technology. Continuous support from the government and related institutions is needed in terms of training, access to capital, and digital export facilitation so that Indonesian MSMEs can compete in the global market in a sustainable manner.